MicroRNA-29b-3p Promotes Human Retinal Microvascular Endothelial Cell Apoptosis via Blocking SIRT1 in Diabetic Retinopathy - Zeng, Yong; Cui, Zekai; Liu, Jian; Chen, Jiansu; Tang, Shibo (Frontiers in Physiology, 2020)
Background: Diabetic retinopathy (DR) is a main complication of diabetes mellitus (DM). Recent studies have implicated microRNAs in human retinal microvascular endothelial cell (HRMEC) dysfunction. In this study we aim to investigate the apoptotic promotion of miR-29b-3p by blocking SIRT1 in HRMEC for DR situation. Method: Blood samples were obtained from DR patients and controls. Dual-luciferase reporter assay using HEK-293T cells was performed to show the direct interaction of miR-29b-3p and the 3’UTR of SIRT1. HRMECs were exposed to 5.5 mmol/L glucose (normal control), 5.5 mmol/L glucose and 24.5 mmol/L mannitol (osmotic pressure control), 30 mmol/L glucose (hyperglycemia, HG), 150 μmol/L CoCl2 (hypoxia), 30 mmol/L glucose plus 150 μmol/L CoCl2 (HG-CoCl2). To identify the regulating relationship between miR-29b-3p and SIRT1, HRMECs were transfected with miR-29b-3p mimics/inhibitors or their negative controls. SRT1720 was used as SIRT1 agonist. Cell viability was assessed with the cell counting kit-8 (CCK-8) assay and apoptotic cells were stained by one step TUNEL assay kit. Gene and protein expression were assayed by RT-qPCR and western blotting separately. Result: MiR-29b-3p was upregulated to 3.2 folds and SIRT1 protein was downregulated to 65% in DR patients. Dual-luciferase reporter assay showed the direct interaction of miR-29b-3p and SIRT1. HRMECs were identified as >95% positive for CD31 and vWF. MiR-29b-3p and Bax/Bcl-2 ratio was upregulated, while SIRT1 was downregulated in HRMECs in HG-CoCl2 condition. Decreased cell viability and upregulated apoptosis were also found in HRMECs of HG-CoCl2 condition. Upregulated miR-29b-3p decreased the expression of SIRT1 and increased the ratio of Bax/Bcl2. While downregulated miR-29b-3p increased the expression of SIRT1 protein and downregulated the ratio of Bax/Bcl2. SRT1720 rescued miR-29b-3p induced HRMEC apoptosis via upregulating the expression of SIRT1 protein. Conclusion: The dysregulation of miR-29b-3p/SIRT1 is a potential mechanism of HRMEC apoptosis in DR. MiR-29b-3p/SIRT1 may be a potential therapeutic target to DR.